2020
DOI: 10.1080/16549716.2019.1694745
|View full text |Cite
|
Sign up to set email alerts
|

The risk of corruption in public pharmaceutical procurement: how anti-corruption, transparency and accountability measures may reduce this risk

Abstract: Background: The goal of the public procurement of pharmaceuticals is to purchase sufficient quantities of high-quality pharmaceuticals at cost-effective prices for a given population. This goal can be undercut if corruption infiltrates the procurement process. Good procurement practices can help mitigate the risks of corruption and support equitable access to affordable and high-quality medicines. Objectives: This paper aims to 1) examine manifestations of corruption in the pharmaceutical procurement process a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 15 publications
4
70
0
2
Order By: Relevance
“…Corruption is defined by the leading global anticorruption organization, Transparency International, as, "the misuse of entrusted power for private gain" [6]. It is a global phenomenon that manifests in different forms and within all types of organizations [7]. Corruption can foster inequities as it skews how resources are distributed and create access barriers to public services and goods, such as essential medicines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corruption is defined by the leading global anticorruption organization, Transparency International, as, "the misuse of entrusted power for private gain" [6]. It is a global phenomenon that manifests in different forms and within all types of organizations [7]. Corruption can foster inequities as it skews how resources are distributed and create access barriers to public services and goods, such as essential medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the good procurement of pharmaceuticals supports access to essential medicines for the population. Yet, when corruption infiltrates the pharmaceutical procurement processes, health goals can be threatened by possible consequences such as pharmaceutical shortages, inflated drug prices, and the distribution of falsified and substandard essential medicines [7]. Procurement is thus critical to efforts by governments to ensure equitable access of essential medicines for their populations, particularly during these unprecedented times of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…It is important, therefore, to educate States and stakeholders about the ways in which the UPR review process can highlight corruption risks as a barrier to the right to health, and to identify more specific recommendations that might be helpful. For instance, the UPR process could be more specific and explicitly ask countries to make the procurement process open, transparent and free of corruption [44]. In the subsequent review, States would then submit specific measures they have taken in response.…”
Section: Discussionmentioning
confidence: 99%
“…Social audits are ways of measuring, understanding, reporting and ultimately improving an organization's social and ethical performance. These audits create greater accountability in the health sector by enabling stakeholders, including intended beneficiaries, to participate in improving health planning and delivery [44]. Social audits can review State records, determining whether reported expenditures reflect reality, actualizing the Alma-Ata Declaration's principle of participatory healthcare, and instituting grass roots accountability to counter the loss of faith in governance stemming from corruption.…”
Section: Social Auditsmentioning
confidence: 99%
“…Kohler and Dimancesco argue for the importance of integrating ACTA measures into governance for pharmaceuticals procurement [5]. Their article provides a primer on key factors, types, and examples of corruption in pharmaceutical procurement.…”
Section: Corruption and Procurementmentioning
confidence: 99%